Corruption and non-performing loans - Gjeçi, Ardit (Economic and business review, 2022)
This article empirically evaluates the impact of corruption on the level of non-performing loans (NPLs) using the international bank-level data, spanning over the period 2000e2016 and across 140 countries. We find a positive and statistically significant relationship between corruption and NPLs. We also analyze the channels through which cor- ruption affects NPLs. We find that the relationship between corruption and NPLs becomes more pronounced during and after the global financial crisis and is more pronounced for smaller banks. The association between corruption and NPLs is stronger in countries characterized by a high level of collectivism. The link between corruption and NPLs is higher where the legal environment is weak and where economies are market-based.
Keywords: banke; banks; corruption; credit; korupcija; krediti